2020
DOI: 10.1155/2020/8827705
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature and Water on Mechanical Properties, Energy Dissipation, and Microstructure of Argillaceous Sandstone under Static and Dynamic Loads

Abstract: RMT-150B rock mechanics and split Hopkinson pressure bar (SHPB) devices were adopted to investigate the physical and mechanical properties, energy dissipation, and failure modes of argillaceous sandstone after different high temperatures under air-dried and saturation states. In addition, SEM and EDS tests were conducted to investigate its microstructure characteristics. Results showed that both the P-wave velocity and density of argillaceous sandstone specimen decreased with the increase of high temperature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…When temperature increases from 25°C to 900°C, the P-wave velocity decreases from 3982 m/s to 2646 m/s, with a larger decrease of 33.56%, while its porosity increases by 182% after 900°C treatment compared with that at 25°C. This phenomenon is attributed to the thermal expansion of mineral particles and water vaporization of deep sandstone after hightemperature treatment, which is treated as thermal damage [25,26]. Particularly, Jin et al [27] investigated the inner structure and composition change of sandstone after different high-temperature treatments and found that when the temperature was higher than 500°C, the propagation of the original cracks at the boundary of different mineral particles increases and more new cracks are formed significantly due to the internal thermal stress caused by the nonuniform expansion of mineral particles.…”
Section: Analysis Of Test Resultsmentioning
confidence: 99%
“…When temperature increases from 25°C to 900°C, the P-wave velocity decreases from 3982 m/s to 2646 m/s, with a larger decrease of 33.56%, while its porosity increases by 182% after 900°C treatment compared with that at 25°C. This phenomenon is attributed to the thermal expansion of mineral particles and water vaporization of deep sandstone after hightemperature treatment, which is treated as thermal damage [25,26]. Particularly, Jin et al [27] investigated the inner structure and composition change of sandstone after different high-temperature treatments and found that when the temperature was higher than 500°C, the propagation of the original cracks at the boundary of different mineral particles increases and more new cracks are formed significantly due to the internal thermal stress caused by the nonuniform expansion of mineral particles.…”
Section: Analysis Of Test Resultsmentioning
confidence: 99%